Bridge Maintenance Prioritization and Condition Rating Based on Fermatean Fuzzy AHP Approach - Salsabeel Sahib Jafar; Sawsan Rasheed Mohammed (Civil Engineering Journal, 2026)
Bridges are considered critical components of transportation infrastructure and play an integral role in public welfare and economic development. Bridge authorities in Iraq face multiple challenges in maintaining the efficiency and serviceability of the bridge network while developing a maintenance plan within limited budgets. Thus, this study aims to develop a systematic condition assessment methodology as a tool to prioritize maintenance projects and optimize available budgets to enhance the management of bridge networks. For this purpose, the bridge structure is broken down into four components: deck, superstructure, substructure, and accessories, and each component is divided into a number of elements. Bridge maintenance experts were surveyed to assign weights for the identified components and elements using the Fermatean fuzzy Analytic Hierarchy Process (FF-AHP). The weighted averaging approach was then used to aggregate components' condition ratings with expert-determined weights to obtain the overall Bridge Condition Index (BCI) of each bridge. Bridges with the lowest BCI get higher priority for maintenance. The proposed methodology was applied to thirteen bridges in Baghdad to demonstrate its practicality. The results indicate its reliability and capability to evaluate and rank bridges based on their urgency for maintenance. The proposed method would help bridge engineers and policymakers to make informed maintenance investment decisions during the budget allocation process.